1972
DOI: 10.1172/jci107131
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Iron in the Pathogenesis of Porphyria Cutanea Tarda

Abstract: A B S T R A C T Porphyria cutanea tarda (PCT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…However, the pattern of (6)(7)(8)(9), and a previous report from our laboratory demonstrated that ferrous ion was a potent inhibitor of hepatic COSYN activity (10). The present report describes the inhibitory effect of ferrous ion on hepatic URODE-CARB activity.…”
Section: Introductionmentioning
confidence: 48%
See 1 more Smart Citation
“…However, the pattern of (6)(7)(8)(9), and a previous report from our laboratory demonstrated that ferrous ion was a potent inhibitor of hepatic COSYN activity (10). The present report describes the inhibitory effect of ferrous ion on hepatic URODE-CARB activity.…”
Section: Introductionmentioning
confidence: 48%
“…In a previous report in which porphyrin synthesis in mitochoncria-free crude liver extracts was studied, it was noted that the synthesis of COPRO was gradually inhibited by increasing concentrations of ferrous ion (10). Maximal inhibition occurred at iron concentrations of 0.08-0.3 mM.…”
Section: Resultsmentioning
confidence: 94%
“…An increase in the synthesis of uroporphyrinogen despite normal ALA synthetase activity suggests a regulatory mechanism later in the heme biosynthetic pathway. We previously reported that, under conditions which inhibit both URODECARB and uroporphyrinogen III cosynthetase (heating or the addition of ferrous iron) uroporphyrin synthesis from porphobilinogen in crude liver extracts was greatly increased (17). These studies suggest a regulatory effect on uroporphyrinogen I synthetase activity by URODECARB and(or) uroporphyrinogen III cosynthetase.…”
Section: Introductionmentioning
confidence: 91%
“…alters hepatic porphyrin metabolism in a way that parallels the abnormalities observed in PCT (17). However, the vast majority of patients with alcoholic liver disease and hepatic siderosis do not develop PCT. This clinical observation has led to speculation that patients with PCT have an occult genetic abnormality expressed only when the liver cell is injured in a specific way (18).…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies synthase. 51 However, this effect was only produced in vitro suggest that the ratio of transferrin receptor/serum ferritin in the presence of rather high and nonphysiological concenprovides the best estimate of the iron status of a healthy trations of iron and has not been confirmed by further studpopulation and is the most reliable parameter for distinguish-ies. Thus, its clinical importance or physiological occurrence ing iron deficiency anemia from the anemia of chronic dis-is far from established.…”
Section: 13mentioning
confidence: 97%